NUTQ KAMCHILIGIGA EGA BO’LGAN BOLALAR BILISH FAOLIYATI XUSUSIYATLARI - Ikramova Dilafruz Furqat qizi, Suvankulova Shahnoza Karimqulovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The specificity of the development of a child's speech,the violation of basic functions in speech,the influence of speech impairment on cognitive activity, the influence of phonemic impairment of perception on speech impairment,the importance of the use of games in eliminating speech impairment.